The struggle for control of American military aviation - Larson, Paul Harris (Kansas State University, 2016)
The United States Army activated the Aeronautical Division, United States Signal Corps, on August 1, 1907. The men of the Aeronautical Division faced hardships and challenges from the very beginning as they tried to build the nation’s first air force prior to World War I. The U.S. Army, the War Department, Congress, and even the American people, really did not know what aircraft could do beyond simple flight. American airmen tried to demonstrate what air power was capable of, but the response to their achievements never met their expectations. Using an abundance of primary and secondary sources on American air power, this dissertation demonstrates that airmen’s struggle for a separate service was not something that developed slowly over the course of decades. Instead, this dissertation shows that airmen wanted independence from the U.S. Army from the start. From their point of view, the U.S. Army, the War Department, and Congress never really appreciated or understood air power. As a result, airmen became more and more alienated with each passing year until they achieve want they wanted -- independence.
Keywords: History; Air power; Billy Mitchell; Air Force; Aviation